2011
DOI: 10.1590/s0365-05962011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Mesoterapia: uma revisão bibliográfica

Abstract: Intradermotherapy is a medical procedure introduced by Pistor in 1958 that consists in the application of intradermal injections of diluted pharmacological substances that are given directly into the region to be treated. There are reports of the use of intradermotherapy to treat painful diseases, skin diseases and unaesthetic conditions. Medical clinics have been recently offering the treatment of intradermotherapy, using the more popular name for this practice -mesotherapy. There is only scant scientific inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
1
8
0
18
Order By: Relevance
“…These results were confirmed with the intradermal inoculation of procaine and penicillin G [24, 25]. Similar results were demonstrated in human studies following intradermal injection (up to 4 mm), and interestingly results confirmed that when a drug is injected at a depth of more than 10 mm it remains for a short time in the surrounding tissues and reaches the systemic circulation rapidly [6]. …”
Section: Reasons To Consider Mesotherapy In Pain Managementsupporting
confidence: 72%
See 2 more Smart Citations
“…These results were confirmed with the intradermal inoculation of procaine and penicillin G [24, 25]. Similar results were demonstrated in human studies following intradermal injection (up to 4 mm), and interestingly results confirmed that when a drug is injected at a depth of more than 10 mm it remains for a short time in the surrounding tissues and reaches the systemic circulation rapidly [6]. …”
Section: Reasons To Consider Mesotherapy In Pain Managementsupporting
confidence: 72%
“…The use of a single drug appears to reduce the risk of drug-drug interactions and local side effects, and the risk of infection is avoided if correct ascetic procedures are employed [5]. Literature reports that the subcutaneous infections [6, 71] seem to be caused by external contamination and malpractice rather than to the technique itself.…”
Section: Adverse Events and Local Reactions To Mesotherapymentioning
confidence: 99%
See 1 more Smart Citation
“… 1 The term “meso” from mesotherapy comes from the Greek word “mesos” referring to the mesoderm (or middle germ cell layer) in the early embryo, which differentiates into tissues and structures, including bone, cartilage, muscle, and connective tissue. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Estos procedimientos no siempre se realizan siguiendo estándares de seguridad e higiene, e incluso son realizados por personal no médico. También es frecuente la aplicación de otras sustancias con las misma técnica, que no están aprobados por entes reguladores y sin registro sanitario 1 .…”
unclassified